(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article explores the key data on the new method of MCA (magnetic compression anastomosis). This topic is both interesting and relevant, as the method has not yet been included in official clinical guidelines (protocols) of most countries, including international standards such as NCCN, ESCP, ASCRS, WSES, etc. However, the situation is evolving, and every quarter new scientific research articles are published worldwide, describing the effectiveness of this surgical technique. Our analysis aims to identify the main reasons why this method has not yet gained wide adoption in pediatric surgery, despite its effectiveness, accessibility, and applicability in a considerable variety of surgical diseases in children under 17 years of age. Literature searches in Chinese and English were conducted in leading scientific databases, from which 20 of the most relevant publications were selected for analysis. Based on this analysis, two main reasons were identified for why MCA is not yet included in clinical protocols: (1) MCA remains insufficiently studied due to the limited number of large-scale clinical trials — most publications are case reports or small case series; (2) there is a lack of reliable data on the long-term effectiveness and safety of the method.